Geodynamic and hydrodynamic conditions of the Urna and Ust‐Tegus oil fields - A. R. Kurchikov; A. G. Plavnik; D. A. Kurchikov (Геодинамика и тектонофизика, 2019)
This paper discusses the productive beds of the Urna and Ust‐Tegus oil fields (West Siberia, Russian) and permeability and capacity properties that are influenced by geodynamic processes. Strong tectonic processes, accompanied by periodic magma intrusions, produced numerous fractures and faults in the Jurassic sediments, which act as conduits for groundwater flows, and thus led to the hydrothermal alteration of rocks and changes in the pore space. The data presented in the paper testify to the manifestation of these processes in the modern hydrogeochemical and geothermal conditions of the Jurassic‐Cretaceous sediments within the two oil fields and their vicinity. The petrophysical studies of the core samples and the hydrodynamic studies in the wells confirm that the reservoir properties of the productive strata are considerably heterogeneous. Despite the significant effect of the geodynamic factors, the analysis of the tracer data has not revealed any apparent spatial consistency of the presence (or absence) of a hydrodynamic connection between the wells and the locations of fractured and dynamically stressed zones. In our study, we have proposed and tested a method based on the analysis of morphotectonic features detectable in the depth maps of reference surfaces. This method is a useful additional tool for discovering and analyzing the relationships between the tectonic and hydrodynamic conditions of oil and gas fields.